Coexistence of borderline ovarian epithelial tumor, primary pelvic hydatid cyst, and lymphoepithelioma-like gastric carcinoma - Tayfun Gungor; Sunduz Ozlem Altinkaya; Levent Sirvan; Roberto Alvarez Lafuente; Serdar Ceylaner (Elsevier, 2011)
Objectives: Borderline ovarian tumors (BOTs) represent a heterogeneous group of ovarian epithelial neoplasms. Despite a favorable prognosis, 10-20% of BOTs exhibit progressively worsening clinic. Primary involvement of pelvic organs with echinococcus is very rare. Lymphoepithelioma-like gastric carcinoma is a rare neoplasm of the stomach. Case Report: A 58-year-old woman referred with abdominal swelling and gastric complaints. Imaging studies revealed a huge cystic mass with multiple septations and solid component, another cystic mass with an appearance of cyst hydatid in the pelvis, and thickening of the small curvature of stomach. Gastroscopy revealed an ulcer with a suspicious malignant appearance, and histology of the endoscopic specimen showed severe chronic inflammation and lymphocytic infiltration. No other involvement of hydatid cyst was detected. In the exploration, there was a 25 cm cystic lesion with solid components arising from right ovary, another 6 cm cyst over the former, 7 cm cystic lesion arising from left ovary, and 10 cm mass near the small curvature of the stomach. Excision of the masses; total gastrectomy with esophagojejunal anastomosis; total abdominal hysterectomy; bilateral salpingo-oophorectomy; omentectomy; appendectomy; splenectomy; and pelvic, paraaortic, and coeliac lympadenectomy were performed. Final pathology revealed lymphoepithelioma-like gastric carcinoma, bilateral serous BOT, and hydatid cyst. Discussion: Hydatid cyst should always be considered in the differential diagnosis of abdominopelvic masses in endemic regions of the world. Preoperative diagnosis of primary pelvic hydatid disease is difficult and awareness of its possibility is very important especially in patients residing in or coming from endemic areas.